'Hindu Communism': Satyabhakta, apocalypses and utopian Ram Rajya. (April 2021) - Gupta, Charu
In the north India of 1920s–30s, many first-generation anticolonial communists and Left intellectuals did not see any contradiction in reliance upon religion, ethical traditions and morality in a search for vocabularies of dignity, equality, just polity and social liberation. Through select writings in Hindi of Satyabhakta (1897–85), an almost forgotten figure in histories of communism in India, this article focuses on the entanglement between religion and communism as a way of thinking about the Left in India, and the problems and possibilities of such imaginings. Steeped in a north Indian Hindi literary print public sphere, such figures illuminated a distinctly Hindu and Indian path towards communism, making it more relatable to a Hindi–Hindu audience. The article draws attention to Satyabhakta's layered engagements with utopian political desires, which, in envisaging an egalitarian future, wove Hindu faith-based ethical morality, apocalyptic predictions and notions of a romantic Ram Rajya, with decolonisation, anti-capitalism and aesthetic communist visions of equality. Even while precarious and problematic, such imaginations underline hidden plural histories of communism and, at the same time, trouble atheist, secular communists as well as the proponents of Hindutva.